About one more Organ of the Stalinist Period – Troikas and Petiorkas - Starkauskas, Juozas (Genocidas ir rezistencija, 2002)
Informal formations of party and chekist organs – troykas, chetvyortkas, petyorkas – were formed on the instructions of the Lithuanian Bureau of the Central Committee of the Communist Party of Lithuania (LKP(b)); they began their more active operations after the 7th assembly of the Central Committee of the Lithuanian Communist Party (LKP(b) CK), held on 23–24 August 1945. The task of these formations was to combine chekist military measures with administrative, economic, political, etc. measures, mobilising the efforts of the occupation structures and collaborators, to crush primarily the armed resistance. The troykas, chetvyortkas, petyorkas in 1945–1947 were more suited than the regional party bureaux to wage fight against the resistance because, being smaller and more specialised, they were able to deal with more classified and operational issues and to adopt more urgent decisions. By their decisions to crush the underground, the troykas and petyorkas often contributed to the strengthening of the communist terror against the peaceful population. In particular, the confiscation of property from the families of partisans and their alleged supporters was often practised, and people were arbitrarily classified as such.